P230 CARDIOGENIC SHOCK NETWORK: FROM PRIMARY PERCUTANEOUS CORONARY INTERVENTION TO VENTRICULAR ASSIST DEVICE IMPLANTATION. (18th May 2022) - Sorini Dini, C; Maccherini, M; Bernazzali, S; Natali, B; Codecasa, R; Antenore, A; Bellandi, F; Valente, S
Abstract: : We report the clinical case of a 75 year–old man, previous smoker with mild lower extremity arterial disease, that presented a sudden and intensive chest pain. The emergency medical system documented an anterior STEMI quickly complicated by out–of–hospital cardiac arrest from a shockable rhythm, treated with DC–shock with rapid ROSC and recovery of consciousness. The patient was transported to the local hospital where coronary angiography showed extensive intraluminal thrombosis of ostial Cx and ostial LAD treated with thrombus aspiration and balloon angioplasty. During the procedure the patient was supported with inotropic agents, mechanical ventilation and IABP for a cardiogenic shock. After few hours he was transferred to level II hospital, equipped with all mechanical circulatory supports (MCS) and on–site cardiac surgery, where he was assisted with vaso–inotropic drugs, Impella CP and continuous renal replacement (CRRT). After 3 days for a refractory cardiogenic shock (stage D) the patient was referred and then transferred to our hospital, a level III hospital with cardiac transplantation program, for hemodynamic stabilization and eventual long term ventricular assist device (VAD). After 5 days the patient was weaned by Impella support, then weaned by mechanical ventilation, renal replacement therapy, without any neurological damage. The echocardiography showed a severe left ventricular dysfunction (EF 20%) with severe mitral regurgitation with good right ventricle function, confirmed also by strain assessment. In the following weeks were reported repeated episodes of pulmonary congestion treated with high doses of diuretics, NIV and nitroprusside infusion and episodes of low cardiac output treated with inotropes for prolonged periods. Mitraclip implantation was technically feasible but Heart Team decided to implantation an LVAD due to numerous episodes of low cardiac output and reduced cardiac index values. Screening for VAD showed no contraindications, therefore after 72 days from acute event LVAD was implanted with positive outcome. Conclusion: the presence of a local network for cardiogenic shock allowed to optimize the clinical pathway of this patient and to manage in an integrated way the complex treatment of cardiogenic shock.